Brucella infection of the thoracic vertebral arch presenting with an epidural abscess: a case report. (December 2015) - Yin, ZhiXun; He, ErXing; Ding, HongMei; Chen, JingChen
Abstract Introduction AlthoughBrucella spondylitis andBrucella discitis have been frequently reported, Brucella infection of the vertebral arch is rare and has not been previously described. We present the first case ofBrucella infection of the thoracic vertebral arch with epidural abscess formation and discuss the clinical key points. Case presentation A 57-year-old man of Han nationality with a history of contact with an isolated sheep stomach 2 months previously was admitted with an undulant fever, night sweats, back pain, and weakness. Thoracic magnetic resonance imaging showed laminar destruction of T9 and an epidural abscess at the T9 to 10 level with significant cord compression. Diagnosis ofBrucella infection of his vertebral arch was confirmed by a positive blood culture with growth ofBrucella melitensis . Total laminectomy, abscess cleansing, and percutaneous pedicular screw fixation was performed initially, followed by antibiotic treatment with a combination of doxycycline and rifampin for 4 months. Recovery was confirmed by clinical, magnetic resonance imaging, and blood culture findings. Conclusions This is an unusual case ofBrucella infection of the vertebral arch with epidural abscess formation. Effective antibiotic therapy of a sufficient duration and timely performance of surgical treatment are the key points in management of such cases.